Respostas

2014-07-17T19:54:34-03:00
Resolvendo por Baskara :
D = delta

A ) D = 49 - 4.6.1
D = 49 - 24
D = 25

X = 7 (+/-) 5 ÷ 12

X ' = 12 / 12 = 1
x" = 2 / 12 = 1/6

B ) D = 169 - 144
D = 25

X = 13 (+/-) 5 ÷ 2

X ' = 18 / 2 = 9
X" = 8 / 2 = 4
2014-07-17T20:11:28-03:00
A) 6x² - 7x + 1 = 0
a = 6
b = -7
c = 1
      Δ = b² - 4ac
      Δ = (-7)² - 4 * 6 * 1
      Δ = 49 - 24
      Δ = 25
               x = - b ± √Δ / 2a
               x = - (-7) ± √25 / 2 * 6
               x' = 7 - 5 / 12 = 2 / 12 = (simplificando [dividindo] ambos por 2) = 1 / 6
               x'' = 7 + 5 / 12 = 12 / 12  = 1
As raízes da equação são 1 / 6 e 1.
                      
B) x² - 13x + 36 = 0
       Δ = (-13)² - 4 * 1 * 36
       Δ = 169 - 144
       Δ = 25
               x = - (-13) ± √25 / 2 * 1
               x' = 13 - 5 / 2 = 8 / 2 = 4       
               x'' = 13 + 5 / 2 = 18 / 2 = 9
As raízes da equação são 4 e 9.

Espero ter ajudado. Valeu!

3 3 3